2021
DOI: 10.1038/s41598-021-81718-2
|View full text |Cite
|
Sign up to set email alerts
|

Phanerozoic radiation of ammonia oxidizing bacteria

Abstract: The modern nitrogen cycle consists of a web of microbially mediated redox transformations. Among the most crucial reactions in this cycle is the oxidation of ammonia to nitrite, an obligately aerobic process performed by a limited number of lineages of bacteria (AOB) and archaea (AOA). As this process has an absolute requirement for O2, the timing of its evolution—especially as it relates to the Great Oxygenation Event ~ 2.3 billion years ago—remains contested and is pivotal to our understanding of nutrient cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 85 publications
0
16
4
Order By: Relevance
“…Angelarchaeales likely occur in a variety of soils and sediments where they have so far gone undetected using primer based CuMMO survey methods. Thus, this new clade of CuMMOs provides an opportunity for further study of these enzymes, and for molecular clock-based analyses of their evolution relative to Earth history [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Angelarchaeales likely occur in a variety of soils and sediments where they have so far gone undetected using primer based CuMMO survey methods. Thus, this new clade of CuMMOs provides an opportunity for further study of these enzymes, and for molecular clock-based analyses of their evolution relative to Earth history [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antiquity of rTCA in NOB relative to Chlorobi is further consistent with the higher sequence-level diversity of rTCA proteins such as ATP citrate lyase in NOB (>75% similarity between sequences from Chlorobi, >65% between Nitrospirota, as low as ~53% between Nitrospinota), consistent with NOB having radiated over substantially longer evolutionary timescales than rTCA-encoding Chlorobi. This is possibility is supported by molecular clock studies that have placed the radiation of Nitrospirota and Nitrospinota >1.5 Gya [ 31 ].…”
Section: Resultsmentioning
confidence: 93%
“…Phylogenetic placement of Cyc2 Cytochromes from Chlorobi are in a fairly derived position, sister to a clade made up of iron oxidizing Betaproteobacteria such as Gallionella and Sideroxydans , nested within a broader radiation of proteobacterial sequences. Recent molecular clock estimates for the antiquity of Zeta- and Beta-proteobacteria suggest that these clades are less than ~1.8 Ga, with crown group Proteobacteria ~2.2 Ga [ 31 ]; together with our results here, this suggests that much if not all of the diversity of neutrophilic iron oxidizing bacteria that utilize Cyc2 Cytochrome homologs have radiated after the Great Oxygenation Event ~2.3 Gya when aerobic metabolisms first became viable due to the accumulation of significant atmospheric O 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be found only in a limited number of bacteria and archaea. A recent phylogenomic analysis suggested that AOA originated from the terrestrial non-ammonia-oxidizing ancestors and expanded to the shallow and then deep ocean upon their oxygenation ( Ren et al, 2019 ), while ammonia-oxidizing bacteria are much younger ( Ward et al, 2021 ). Note however that this model is still under discussion ( Abby et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%